Analysis of Knowledge, Understanding and Skills of Physics Teachers of State Senior High Schools in Developing and Analyzing Test Items - Yusrizal, Y.; Suliyanah, S.; Basri, T. H. (Jurnal Pendidikan IPA Indonesia, 2017)
This study is aimed to determine the level of knowledge and understanding of physics teachers to the evaluation of learning and to describe the physics teachers’ skills in constructing and analyzing items. This type of research is quantitative descriptive, the technique of data collection is done by survey method using a developed questionnaire instruments. The population in this study is all physics teachers of Senior High School throughout the city of Banda Aceh. Those became the samples were 32 physics teachers of Senior High School randomly selected. The data obtained were analyzed descriptively. The results showed that only physics teachers of SMAN 4, SMAN 7, SMAN 8, SMAN 10 and SMAN 13 Banda Aceh who have very high category of knowledge and understanding level of the learning evaluation and the skills of physics teachers of Senior High School in Banda Aceh in constructing and analyzing the test items have not been satisfactory.